The effects of long COVID-19, its severity, and the need for immediate attention: Analysis of clinical trials and Twitter data - Bhattacharyya, Arinjita; Seth, Anand; Rai, Shesh (Frontiers in Big Data, 2022)
Background: The coronavirus disease 2019 (COVID-19) has been declared a pandemic since March 2020 by the World Health Organisation Identifying the disease progression, predicting patient outcomes early, the possibility of long-term adverse events through effective modeling, and the use of real-world data are of immense importance to effective treatment, resource allocation, and prevention of severe adverse events of grades four or five. Methods: Firstly, we raise awareness about the different clinical trials on Long covid-19. The trials were selected with long Covid-19 available in ClinicalTrials.Gov. Secondly, we analyze the recent tweets on Long haul covid-19 and give an overview of the sentiments of the people. Th tweets obtained with the term #long covid-19 consisted of 8436 tweets. We utilized the NRC Emotion Lexicon method for sentiment analysis. Finally, we analyze the retweet and favorite counts associated with the sentiments of the tweeters via a negative binomial regression model. Results: Our results find that there are two types of clinical trials being conducted observational and interventional. The retweet counts and favorite counts are associated with the sentiments and emotions such as disgust, joy, sadness, surprise, trust, negative, and positive. We need resources and further research in the area of Long Covid-19.